EARLY MOTHERHOOD IN SOWETO: THE NEXUS BETWEEN THE CHILD SUPPORT GRANT AND DEVELOPMENTAL SOCIAL WORK SERVICES - Jordan, Nhlanhla; Patel, Leila; Hochfeld, Tessa (Social Work/Maatskaplike Werk, 2014)
In this article we ask whether the child support grant can mitigate the vulnerability of early motherhood, and if so, in what ways and what are its limits. Using data from a study on CSGs in a poor urban area of Johannesburg, we report on the circumstances of young women recipients. We find that the grant has positive outcomes for the women, but these are limited in the face of the range of needs and support necessary to give the young women a chance to successfully negotiate both motherhood and their own transition to adulthood. We suggest areas where social workers can engage positively with these issues